In Pursuit of Sustainable Strategic Long-term Planning Throughout Meta-postmodernism as New Perspective of Stylistic Design - Nikoofam, Mojdeh; Mobaraki, Abdollah (Anglo-American Publications LLC, 2017)
During the different period of architectural design, designers attempt to achieve high level of life quality for all users. Architecture and urban planner want to provide a style of design which not only achieves different function for different users with respect to their ethnicity, ability, age, sex, capability, position, and life style but also improve friendly environment throughout responsive legislation based on long-term planning. Although, the styles are considered some indicators, it is ignored the other important characteristics. Therefore, the existing styles never achieve standard level of satisfaction of different people. The goal of the research is to introduce meta-postmodern style as supplement stylistic approach. The style tries to consider all important indicators that create a strategic long-term planning for different generations. Various characteristics of new style can be applied to improve the quality of human life and provide a health, livable and sustainable planning for all users.